Dietary strategy to reduce methane emission in Brazilian beef cattle production - Lima, Jacqueline Geraldo de (2014)
In Brazil, estimate of methane (CH4) emission for the National Greenhouse Gas Inventory is carried out using the empirical Tier 2 approach published by the Intergovernmental Panel on Climate Change (IPCC). Although, IPCC recommends the use of a more specific, mechanistic Tier 3 approach, this is hampered by a lack of consolidated data for development, evaluation and application of such a Tier 3 approach. The purpose of the present modelling study was to evaluate whether a Tier 3 approach instead of the Tier 2 approach has merit in estimating the effect of improvement of diet quality by feeding supplements on CH4 emission, calculated by both a Tier 2 and an extant Tier 3 approach. Six systems of beef cattle production in Brazil were considered which differed inage at slaughter mainly due to diet quality (ranging from 14 to 44 months). The systems studied encompass most of the range of slaughter age and feeding methods observed and the differences between them can be considered realistic for variation in current Brazilian practice of beef production. Estimates of feed quality and animal performance were based on published Brazilian studies and on data from a Brazilian inventory on enteric CH4. Both Tier 2 and Tier 3 approaches estimated a large variation in CH4 emission for the six production systems. The highest level of enteric CH4 emission (168 and 145 kg per slaughtered animal, estimated with the Tier 2 and Tier 3 approach, respectively) was estimated for the system with slaughter after 44 months and the lowest with slaughter after 14 months (35 and 31 kg per slaughtered animal, estimated with the Tier 2 and Tier 3 approach, respectively). The general trend was a profound increase of CH4 emission with increase of age-at-slaughter. Methane estimates depended strongly on the modelling approach adopted. Using the Tier 3 approach in the present study with the assumptions made for the six Brazilian beef production systems indicated substantially lower estimates of enteric CH4 compared to the IPCC Tier 2 approach. The Ym values (fraction of gross energy intake emitted as CH4) estimated by the Tier 3 approach for separate growing periods (seasons) within the different systems ranged between 0.044 and 0.070, and between 0.049 and 0.058 when averaged for the whole growing period (cf. 0.065 with Tier 2). Model estimates should be confirmed by evaluation against independent in vivo data obtained under local Brazilian conditions of beef production.